(untitled) (Docentes 2.0 Journal, 2021)
Life and education are human rights established in the Declaration of Human Rights (Human Rights) document in which the United Nations Organization (UN) conceived in 1948. Until then, in Venezuela, the Institutions of University Education (IEU) carried out their functions in person, even though some had started learning processes mediated by technology. As a result, a proposal was generated under an integrating vision of four (4) dimensions: 1) Systematization of the information, 2) Staff training, 3) Articulation of the actors, 4) Monitoring and control of the model. Based on the preceding, the Academic Vice-Rector of the José Antonio Páez University diagnosed the administrative needs of the plan, establishing the objective of designing a digital management model to guarantee the continuity of university processes, both academic and administrative. The type of research was descriptive, with a documentary design, applied to a sample of four (4) faculties and two (2) general directorates. The evidence showed that the systematization of information and the staff training in administrative processes are crucial to university management, which was optimized by incorporating technology, concluding that when management theories are merged with digital tools, they are developed in an efficient university management process.